Management of pericardial fluid in blunt trauma: Variability in practice and predictors of operative outcome in patients with computed tomography evidence of pericardial fluid. Issue 4 (April 2017) - Witt, Cordelie E.; Linnau, Ken F.; Maier, Ronald V.; Rivara, Frederick P.; Vavilala, Monica S.; Bulger, Eileen M.; Arbabi, Saman
Abstract : BACKGROUND: The objectives of this study were to assess current variability in management preferences for blunt trauma patients with pericardial fluid, and to identify characteristics associated with operative intervention for patients with pericardial fluid on admission computed tomography (CT) scan. METHODS: This was a mixed-methods study of blunt trauma patients with pericardial fluid. The first portion was a research survey of members of the Eastern Association for the Surgery of Trauma conducted in 2016, in which surgeons were presented with four clinical scenarios of blunt trauma patients with pericardial fluid. The second portion of the study was a retrospective evaluation of all blunt trauma patients 14 years or older treated at our Level I trauma center between January 1, 2010, and November 1, 2015, with pericardial fluid on admission CT scan. RESULTS: For the survey portion of our study, 393 surgeons responded (27% response rate). There was significant variability in management preferences for scenarios depicting trace pericardial fluid on CT with concerning hemodynamics, and for scenarios depicting hemopericardium intraoperatively. For the separate retrospective portion of our study, we identified 75 blunt trauma patients with pericardial fluid on admission CT scan. Seven underwent operative management; six of these had hypotension and/or electrocardiogram changes. In multivariable analysis, pericardial fluid amount was a significant predictor of receiving pericardial window (relative risk for one category increase in pericardial fluid amount, 3.99, 95% confidence interval, 1.47–10.81) but not of mortality. CONCLUSION: There is significant variability in management preferences for patients with pericardial fluid from blunt trauma, indicating a need for evidence-based research. Our institutional data suggest that patients with minimal to small amounts of pericardial fluid without concerning clinical findings may be observed. Patients with moderate to large amounts of pericardial fluid who are clinically stable with normal hemodynamics may also appear appropriate for observation, although confirmation in larger studies is needed. Patients with hemodynamic instability should undergo operative exploration. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV. Abstract : Supplemental digital content is available in the text.